2019
DOI: 10.3390/info11010019
|View full text |Cite
|
Sign up to set email alerts
|

Course Analysis of Library and Information Science in Korea

Abstract: Curriculums play a key role in implementing the educational goals and directions of a university. Universities regularly update their curriculums to actively respond to internal and external environmental changes. Korean universities face challenges, including a steady decline in enrollment and demand-oriented convergence education. Because of the nature of convergence science, library and information science should respond more actively to new challenges. This study analyzes the current status of library and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 18 publications
0
5
0
Order By: Relevance
“…It seeks to 1) assess whether gender disparities among librarians manifest in demographic attributes, including age, highest education attained, study program, library type, and length of service; and 2) evaluate the potential association between gender and librarians' self-perceptions of their ICT competencies, as delineated by the 44 SKKNI indicators. The outcomes of this study promise to offer an empirical foundation for the formulation of a tailored LIS curriculum that aligns with the professional requirements of Indonesian librarians, resonating with recommendations by Mo et al (2019).…”
Section: Introductionmentioning
confidence: 76%
“…It seeks to 1) assess whether gender disparities among librarians manifest in demographic attributes, including age, highest education attained, study program, library type, and length of service; and 2) evaluate the potential association between gender and librarians' self-perceptions of their ICT competencies, as delineated by the 44 SKKNI indicators. The outcomes of this study promise to offer an empirical foundation for the formulation of a tailored LIS curriculum that aligns with the professional requirements of Indonesian librarians, resonating with recommendations by Mo et al (2019).…”
Section: Introductionmentioning
confidence: 76%
“…Singh and Shahid (2010) examined LIS education in India and found there was a lack of information technology in LIS education, and Tyagi and Yanthan's (2017) study analyzed the ICT contents of postgraduate degree courses in India, subsequently suggesting a more standardized curriculum which would meet international standards. Wijetunge (2009) identified six subject areas which were taught in most of the LIS programs in Sri Lanka, and Mo, Seon, Park and Kim (2020) analyzed the current status of LIS courses in South Korea. In Europe, Juznic and Badovinac (2005) analyzed changes in LIS curricula in the European Union and reported that LIS schools had changed their curricula to embrace the new generation of professionals.…”
Section: Related Studiesmentioning
confidence: 99%
“…Since a course can be offered in various credit hours, it is difficult to transfer the credit hours into the course numbers. However, according to Table III-41 (2009 and2020) which provided the list of required courses, 4-6 courses were most frequently designated as required courses. From the ALISE reports it is observed that the trend is towards fewer required courses, as more schools have shifted toward fewer required credit hours as a percentage of the total degree.…”
Section: Required Coursesmentioning
confidence: 99%
“…Y. Mo et al (2020) use the term "information science" in a publication dealing with the role and importance of higher education curricula. However, this research is not legal, but bibliographic in nature.…”
Section: Introductionmentioning
confidence: 99%